Clinical Approach in Prosthetic Treatment With 3D-Printed Implant-Retained Removable Denture: DENTCA System - Aleksandar Naydenov; Nikolay Apostolov; Rumen Radev (Hindawi Limited, 2024)
The aim of this study is to present a method that optimizes clinical and laboratory workflow in the fabrication of implant-supported removable dentures by combining conventional and digital protocols. A 73-year-old patient came to our clinic for treatment of a completely edentulous lower jaw. Two Neodent Helix GM implants were placed in the canine regions and a removable denture with Locator GM Novaloc retention elements was fabricated. The DENTCA system was used for impressions, border molding, and to determine both occlusovertical dimension (OVD) and reproducible, physiological position of lower jaw (RPPLJ) in a single clinical visit. In result, we have fabricated a removable denture with implant retention in just two appointments. We can conclude that DENTCA system is a reliable method that allows fabrication of implant-retained removable denture in two clinical visits. The registration of the prosthetic field boundaries, OVD and RPPLJ, combined with CAD technologies, represents a contemporary and accurate method. It takes less time, and expenses are reduced both for the dentist and the patient.